Validação de metodologia de determinação de hidrocabonetos policíclicos aromáticos em águas de produção por microextração em fase sólida. - Vasconcelos, Pedro Hermano Menezes de (2013)
The disposal of water from oil production in the oceans is one of the major environmental problems facing the oil industry and the population, since these compounds have harmful effluents health. Among these compounds, the polycyclic aromatic hydrocarbons (PAHs) stand out. These substances are organic compounds characterized by presenting two or more conjugated aromatic rings. This study evaluated the effect of some parameters on the extraction of PAHs by SPME and subsequent analysis by GCMS using 24 factorial design to optimize the experiments, followed by the analysis of water samples from oil production. It has been found that the technique pre-concentrated samples and the parameters (temperature, PAH concentration, ionic strength, exposure time of the fiber) influence significantly on the amount of PAH extracted, and the effect of each factor depends on the structures of PAHs. The quantitative and qualitative analysis by GCMS was conducted using the technique of distinct fragments in their mass spectra. Four samples were analyzed for water production, using the internal standard method. Conducted to validate the methodology through testing precision, linearity, limits of detection and quantification, and accuracy. The proposed method was efficient, as it showed good reproducibility, linearity satisfactory (correlation coefficients were obtained between 0.9849 and 0.9999), values of LD and LQ compatible with the literature, and an accuracy in the proper concentration range evaluated (recovery values ranged between 84.23 and 148.52%). The factor innovative of the methodology have been able to analyze the PAHs in the samples had very complex arrays without the need for any pretreatment thereof. PAHs of lower molecular masses were, in general, the majority of water in the samples investigated. The total amount of PAH present in all four samples ranged from 30.41 to 170.41 g L-1. The values of the constants calculated distribution indicate that PAHs of higher molecular weights had higher affinity for the polydimethylsiloxane fiber.